ICT tools in intercultural communication pedagogy: their impact on speaking competence and students’ strategies in negotiating meaning - Hasyim, Ruslan; Noni, Nurdin; Nur, Sahril (Frontiers in Education, 2026)
This study examines the role of Information and Communication Technology (ICT) in intercultural communication pedagogy, focusing on its impact on students’ speaking competence and their strategies for negotiating meaning in higher education. Situated in the under-researched context of Southwest Papua, Indonesia, the study addresses a critical gap in existing literature, which has predominantly framed ICT as a technical enhancer of speaking skills while giving limited attention to its mediating role in intercultural interaction, meaning negotiation, and identity expression. Adopting a qualitative case study design, data were collected through classroom observations, semi-structured interviews with 25 English Education students and 3 lecturers, and document analysis within an ICT-mediated Speaking for Intercultural Communication course. The data were analyzed thematically to investigate (1) how ICT-based instruction influences students’ intercultural speaking competence and (2) how ICT tools support learners’ strategies for negotiating meaning, adapting to cultural norms, and expressing identity during intercultural speaking activities. The findings indicate that ICT-based instruction enhances students’ speaking competence by improving linguistic proficiency, reducing speaking anxiety, and increasing confidence and willingness to communicate in intercultural contexts. Furthermore, ICT tools function as mediational resources that enable learners to negotiate meaning through multimodal strategies, manage pragmatic differences across cultures, and articulate local cultural identities through digital storytelling and content creation. These practices reposition speaking activities as sites of cultural mediation rather than merely linguistic performance.